Teaching English Vocabulary for Young Learners through Electronic Guessing Game - Ana, I.K.T.A (Journal of Psychology and Instructions, 2018)
This study was an evaluative study as a part of research and development study which aimed at: (1) describing the benefits and the problems of implementing Electronic Guessing Game in teaching vocabulary; and (2) the studentsâ vocabulary mastery and their achievement motivation after the Electronic Guessing Game Implementation. The researcher collected the data of the study through observation, interview, questionnaire, and test. Since the data were in the form of quantitative and qualitative data, the researchers analyzed the data both qualitatively and quantitatively. The results of the study show that: (1) the benefits of implementing Electronic Guessing Game were: It makes teaching and learning process becomes fun; it activates the students to get involved; it integrates spelling, pronunciation, and meaning; it helps the students to memorize the vocabulary; and the learners like it. While the problems were: it needs sufficient facilities and some technical problems occur during the implementation; (2) the studentsâ vocabulary mastery improved after Electronic Guessing Game Implementation; and (3) most of the students are very motivated in learning vocabulary through Electronic guessing Game.Â